A multiple-valued logic and memory with combined single-electron and metal-oxide-semiconductor transistors. - Inokawa, H. (IEEE Transactions on electron devices)
Devices that combine single-electron and metal-oxide-semiconductor (MOS) transistors are newly proposed as basic components of multiple-valued (MV) logic, such as a universal literal gate and a quantizer. We verified their operation using single-electron and MOS transistors fabricated on the same wafer by pattern-dependent oxidation of silicon. We also discuss their application to an analog-to-digital converter, a MV adder, and MV static random-access memory.